THE ACTION OF TREATMENS WITH MICRONUTRIENS AND BIOACTIVE COMPOUNDS IN STOPPING THE EVOLUTION OF THE PERIODONTAL DISEASE - Doneta Acatrinei; Norina Forna; Bogdan-Stefan Acatrinei; Natalia Rosoiu (Romanian Society of Oral Rehabilitation, 2021)
Periodontal disease is a significant public health concern. Inflammatory oral diseases are periodontal infections, oral mucosal lesions, pulpal and periapical lesions. The etiology is multi-factorial and is usually associated with a microbial origin, often caused by over-consumption of free sugars. However, the role of micronutrients in these processes is now becoming apparent. Trends have shifted to the role of micronutrients in oral inflammation. The progression of periodontal disease and the healing of periodontal tissues can be modulated by nutritional status. There are numerous degenerative changes in the oral mucosa that have been observed during specific micronutrient deficiencies. Attempts have been made to use dietary supplementation of certain micronutrients to treat oral inflammatory lesions in conjunction with their standard treatment procedures. Micronutrient supplementation can be administered orally or topically. The current review provides insight into the role of nutrition in oral inflammatory diseases, including periodontal disorders, oral mucosal lesions, pulpal and periapical lesions.